Management of post-operative wound in dental surgeries using proteolytic enzyme-flavonoid combination of trypsin, bromelain and rutoside: a single-centre experience - Tiwari, Shashank; Khemnar, Bhushan M.; John, James (International Journal of Research in Medical Sciences, 2022)
Background: Appropriate surgical wound management is required to prevent post-operative complications, including delayed wound-healing which may result in increased hospital stay. The present study aimed to evaluate the efficacy and safety of oral administration of a fixed dose combination of trypsin-bromelain-rutoside in the post-operative management after dental surgeries. Methods: The study was a prospective, observational data collection exercise. Hundred subjects undergoing dental surgeries, who were administered trypsin-bromelain-rutoside combination, were observed over a period of 8 days post-surgery. Verbal rating scales were used for grading the pain intensity and extent of swelling, while a 5-point Likert scale was used to evaluate patient- and investigator-reported global assessment of improvement in pain and swelling. Scores at day 3 and day 8 were analysed using paired t test. Results: At day 3 and day 8, the mean scores of pain and swelling were significantly reduced from baseline (all p<0.0001). By day 8, 100% of the patients achieved complete resolution of pain, while mild swelling was reported in only 2 patients. At day 3, 95% patients reported good/ very good global improvement in pain and swelling; while at day 8, 100% reported good/ very good improvement. No adverse event was reported in any of the patients. Conclusions: The study results demonstrate that treatment with trypsin-bromelain-rutoside combination led to significant improvement in the post-operative pain and swelling. The use of this combination is useful for wound recovery and reducing the need for other analgesic and anti-inflammatory drugs.